LEGAL CONSEQUENCES OF TRANSFER OF RIGHTS TO A TRADEMARK THAT HAS NOT BEEN REGISTERED BEFORE THE DEBTOR IS DECIDED BANKRUPT - Ellya Rosa; Endang Prasetyawati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study examines the legal consequences of trademark right transfers that have not been recorded with the Directorate General of Intellectual Property (DJKI) when the seller is subsequently declared bankrupt. The main issue addressed is the legal implications for the buyer (third party) who has legally completed the trademark purchase transaction but has not yet recorded the transfer of rights before the seller was declared bankrupt. The Civil Code, Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, Law Number 20 of 2016 concerning Trademarks and Geographical Indications, and other relevant regulations are all examined in this study using a normative juridical method with statutory and conceptual approaches.